The nurse’s role in the child care with the inborn brittleness of the bones - Stawicka, Agnieszka (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2018)
Introduction Inborn brittleness of the bone - called the osteogenesis imperfecta also, he is included in diseases of the connective tissue, is a hereditary disease, more often appearing at the female sex. Pathological bone fractures result from the defect in the process of coming into existence of the collagen of the type I. This is a genetic disease, heterogenic, because they are inheriting as the autosomal feature dominating, with time recessive, or as the chance mutation. Aim The aim of this work is closer of problems associated with the care and the rehabilitation children touched with disease with which she is inborn brittleness of the bones. Overview Natural-born children with this disease entity have largely immature all arrangements, in which for structure a collagen of the type is participating I. Ciężki constitutes the form of the disease type II- is running from the notable rank with deformations bone, being an effect of fractures of the skeleton in the period of the foetal life and with brittleness very much increased of the bone what is causing fractures as a result of the minimal injuries or the care. For diagnosing illness he most often seeks the foetus in the course of the antenatal. Already in 15 week of pregnancy in an ultrasound scan it is possible to state irregularities talking about the osteogenesis imperfecta. In the same time at the pregnant woman it is possible to perform the amniocentesis, or the biopsy of the amniotic fluid in order to pick up material containing cells of the foetus and to make analyses of producing collagen. Radiological photographs are also detection methods of illness, densitometry bones in the destination of checking their density. In case of the inborn brittleness of the bone he doesn’t have an effective causal treatment so far, only curing is symptomatic - preventing fractures and curing them, the streamlining rehabilitation, relieving pain, the use of medicines and diets of the strengthening bone. Conclusion Issues brought up at this work are essential for the development of children with the inborn brittleness of the bone, the treatment because sufficiently early commenced, the rehabilitation and the correct care led systematically, selected individually for every case, is giving as good results. Early the commenced treatment and the rehabilitation are giving the chance of the better development and prevent complications resulting from illness.